Analisis Mutu Pelayanan Nifas Pertama (Kf1) oleh Bidan di Puskesmas di Kabupaten Pemalang Tahun 2018 - Ragil Sri Pamungkas; Chriswardani Suryawati; Apoina Kartini (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
Maternal Mortality Rate (MMR) in Pemalang Regency in 2017 is still high and happens a lot during childbirth time period (72%). One of the efforts for reducing MMR is the quality service of childbirth for the process of mother and baby recovery, early detection of complications, taking care of and referral of complications. The aim of the study is to determine and analyze the quality of the first childbirth service (KF1) and factors related to the service quality of first childbirth (KF1) by midwives at Health Centres in Pemalang Regency.Quantitative research method used cross sectional research type, sample selection by simple random sampling at 100 civil servant of midwives working period of at least three years in 14 health centres in each sub-district in Pemalang Regency. Data collections were done by questionnaires and observations, data analysis with chi-square statistical tests and multivariate with multiple logistic regression.Research results showed that the service quality of the first childbirth (KF1) is lacking (53%), lacking motivation (54%), less reward (65%), less supervision (50%) and workload according to the standard (57%). Variables related to the service quality of the first childbirth (KF1) are motivation (p-value = 0.018) and rewards (p-value = 0.003). While the variables not related to the service quality of the first childbirth (KF1) are supervision (p-value = 0.229) and workload (p-value = 0.774). The factors that influence the service quality of the first childbirth (KF1) are rewards (value p = 0.031 and OR = 3,466).Suggestions for improving the service quality of the first childbirth (KF1) are midwives have to be more optimal in giving childbirth care and health education, head of health centres can divide the tasks equally among all midwives, midwives in working have to create a positive attitude, the head of the health centres praises the success of childbirth care, the head of the health centres can allocate funds for the transportation of home visits, the implementation of supervision is carried out on a scheduled and routine for all midwives.